2021
DOI: 10.1002/2211-5463.12879
|View full text |Cite|
|
Sign up to set email alerts
|

Withdrawn: MicroRNA‐142‐5p inhibits autophagy in cardiomyocytes in a mouse model of hypoxia/reoxygenation

Abstract: Cardiomyocyte hypoxia-and ischemia-induced apoptosis is a key challenge in the treatment of cardiovascular diseases, and it has been previously reported that high glucose-induced cardiomyocyte apoptosis can be prevented by autophagy activation. Furthermore, down-regulation of the microRNA miR-142-5p protects cardiomyocytes against hypoxia. However, the effects of miR-142-5p on autophagy of myocardial cells under hypoxia/reoxygenation (H/R) are less well understood. Here, we observed that the optimal time for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…For example, a study revealed that miR-101a-3p suppressed H9C2 cell proliferation and, during H/R injury, promoted H9C2 cell apoptosis ( 18 ). Likewise, miR-142-p could promote cell apoptosis in a cardiomyocyte model of H/R injury ( 19 ). Upregulation of miR-221-5p was observed in myocardial hypertrophy and heart failure ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study revealed that miR-101a-3p suppressed H9C2 cell proliferation and, during H/R injury, promoted H9C2 cell apoptosis ( 18 ). Likewise, miR-142-p could promote cell apoptosis in a cardiomyocyte model of H/R injury ( 19 ). Upregulation of miR-221-5p was observed in myocardial hypertrophy and heart failure ( 20 ).…”
Section: Introductionmentioning
confidence: 99%